INTEGRATION OF QUR'ANI VALUES THROUGH THE COFFEE MORNING APPROACH IN CHARACTER EDUCATION LEARNING AT AL RAZI SINAR HARAPAN PRIVATE VOCATIONAL SCHOOL, MEDAN, JOHOR: INTEGRASI NILAI-NILAI QUR’ANI MELALUAI PENDEKATAN COFFEE MORNING DI DALAM PEMBELAJARAN PENDIDIKAN KARAKTER DI SMK SWASTA AL RAZI SINAR HARAPAN MEDAN JOHOR - Mujiono Mujiono; Danny Abrianto (SOSIOEDUKASI, 2025)
This study aims to examine the integration of Qur'anic values through the Coffee Morning approach in character education learning at Al Razi Sinar Harapan Private Vocational School, Medan, Johor. Character education is a national urgency in forming a generation that is not only intellectually superior, but also moral and spiritual. The phenomenon of adolescent moral degradation, such as fights, disrespectful behavior towards teachers, and social ethical crises, emphasizes the need for learning innovations based on religious values. This study uses a descriptive-exploratory qualitative approach with 50 subjects of grades X–XII, which are divided into seven discussion groups. Data was obtained through observation, interviews, and documentation during the implementation of Coffee Morning in July-September 2025. The results of the study show that Coffee Morning is effective in internalizing the values of the Qur'an, including gratitude, honesty, discipline, responsibility, solidarity, and respect for teachers and parents. The relaxed and dialogical atmosphere encourages students to be more open to reflecting on life experiences and relating them to the message of the Qur'an. The impact can be seen in improving discipline, communication skills, learning motivation, spiritual awareness, and social solidarity. Coffee Morning also strengthens the teacher-student relationship and has a positive influence on the family.